REGISTERS IN “SHOPEE & LAZADA”: SOCIOLINGUISTICS AND SEMANTICS STUDY - CM Simatupang, Ervina; Sondang Pardosi, Desi; Zuraida, Ida (International Journal of Psychosocial Rehabilitation, 2020)
Register is the special terminologies or vocabularies used by particular occupation or social groups. It makes the communication is going more interesting because they communicate through special register without its meaning is known by others. There are many registers can be found both written and spoken form, one of them in the online shopping. This research is entitled “Register in ”Shopee and Lazada”: Sosiolinguistics and Semantics study”. The aims of this study are 1) to analyze the functions of registers found in “Shopee &Lazada”, 2) to analyze the meanings appeared in “Shopee & Lazada”. The method used for this research is qualitative-descriptive. The data were taken from “Shopee & Lazada” through online as many as 32. The theory used for analyzing the function of register is Holmes (2013), whereas the theory of register’s meaning based on Catford (1965) and Downing (2006). The findings of this research indicate that the functions of register are divided into 4 types which are, directive, referential, phatic and expressive. The meaning of register are lexical and contextual, and idiomatic.